Infectious Discitis and Spondylodiscitis in Children - Principi, Nicola (Int J Mol Sci, 2016)
In children, infectious discitis (D) and infectious spondylodiscitis (SD) are rare diseases that can cause significant clinical problems, including spinal deformities and segmental instabilities. Moreover, when the infection spreads into the spinal channel, D and SD can cause devastating neurologic complications. Early diagnosis and treatment may reduce these risks. The main aim of this paper is to discuss recent concepts regarding the epidemiology, microbiology, clinical presentation, diagnosis, and treatment of pediatric D and SD. It is highlighted that particular attention must be paid to the identification of the causative infectious agent and its sensitivity to antibiotics, remembering that traditional culture frequently leads to negative results and modern molecular methods can significantly increase the detection rate. Several different bacterial pathogens can cause D and SD, and, in some cases, particularly those due to Staphylococcus aureus, Kingella kingae, Mycobacterium tuberculosis, Brucella spp., the appropriate choice of drug is critical to achieve cure.